2016
DOI: 10.3389/fpls.2016.00821
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy can Confer Superiority to West African Acacia senegal (L.) Willd. Trees

Abstract: Polyploidy is a common phenomenon in the evolution of angiosperms. It has been suggested that polyploids manage harsh environments better than their diploid relatives but empirical data supporting this hypothesis are scarce, especially for trees. Using microsatellite markers and flow cytometry, we examine the frequency of polyploids and diploids in a progeny trial testing four different populations of Acacia senegal, a species native to sub-Saharan regions of Africa. We compare growth between cytotypes and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 55 publications
4
27
0
Order By: Relevance
“…Under both scenarios, the relative fraction of polyploid DOs surviving at the end of the experiment increased with increasing levels of food removal, overcoming the population of nonpolyploid DOs when the environmental challenge introduced in terms of food reduction was strong enough. Taken as whole, these results suggest that WGDs are usually maladaptive under stable environments, but may actually confer an adaptive advantage under certain environmental constraints, which seems in agreement with recent 'real-life' observations (6,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 90%
“…Under both scenarios, the relative fraction of polyploid DOs surviving at the end of the experiment increased with increasing levels of food removal, overcoming the population of nonpolyploid DOs when the environmental challenge introduced in terms of food reduction was strong enough. Taken as whole, these results suggest that WGDs are usually maladaptive under stable environments, but may actually confer an adaptive advantage under certain environmental constraints, which seems in agreement with recent 'real-life' observations (6,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have suggested that polyploids often have a greater chance to survive an extreme environment compared to diploids because they can undergo rapid morphological innovation [5,22,41,42,43,44]. As a pantropical genus, Ceratopteris displays greater heat tolerance and intolerance to cooler temperatures than the temperate taxon [45].…”
Section: Discussionmentioning
confidence: 99%
“…Polyploidization, the duplication of entire genomes either via hybridization between different species (allopolyploidy) or within single species (autopolyploidy), is recognized as an important mode of speciation especially in plants (Estep et al ., 2014; Vamosi et al ., 2018). Polyploids are suggested to have higher genome plasticity (Leitch & Leitch, 2008) allowing adaptation to different environments in both plants (Leitch & Leitch, 2008; te Beest et al ., 2012; Diallo et al ., 2016; Han et al ., 2020) and animals (Schoenfelder & Fox, 2015). Thus, polyploidization can be a first step in ecological speciation and adaptive radiation (Rundle & Nosil, 2005).…”
Section: Major Speciation Models Of Tropical African Biodiversitymentioning
confidence: 99%